Determinants of Intention to Use the Contact Tracing Apps: A Case Study in Northern Cyprus - Adebiyi, Jeremiah Damilola (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Contact tracing is the process of attempting to identify people who have recently been in contact with someone diagnosed with an infectious disease in order to treat them. Digital contact tracing can be described in technological terms as a widely adopted surveillance system that its main purpose is to identify, evaluate and classify potential victims that’s might have been exposed to an infectious disease. This study aims to shed light on a common issue that is generally associated with a contact tracing system, which is privacy. Privacy of citizens is very important and should be highly regarded in situations like this. Getting users to install the contact tracing application is an issue that could be solved by developing an understanding and also mitigation of concerns and tradeoffs of user’s adoption decisions, this study develops a validated extended Technological Acceptance model that proves that privacy concerns is part of the determinants of user’s intention to use contact tracing apps but necessary tradeoffs can be made when it comes for health and safety of the user.

ÖZ: Temaslı takibi, bulaşıcı bir hastalık teşhisi konmuş biriyle yakın zamanda temas halinde olan kişileri tedavi etmek için belirlemeye çalışma sürecidir. Dijital temaslı izleme, teknolojik terimlerle, temel amacı bulaşıcı bir hastalığa maruz kalmış olabilecek potansiyel kurbanları belirlemek, değerlendirmek ve sınıflandırmak olan, yaygın olarak benimsenen bir sürveyans sistemi olarak tanımlanabilir. Bu çalışma, genellikle bir kişi izleme sistemi ile ilişkilendirilen ortak bir sorun olan mahremiyete ışık tutmayı amaçlamaktadır. Vatandaşların mahremiyeti çok önemlidir ve bu gibi durumlarda çok dikkate alınmalıdır. Kullanıcıların kişi izleme uygulamasını yüklemelerini sağlamak, bir anlayış geliştirerek ve ayrıca endişelerin ve kullanıcının benimseme kararlarının değiş tokuşunun azaltılmasıyla çözülebilecek bir sorundur; bu çalışma, gizlilik endişelerinin belirleyicilerin bir parçası olduğunu kanıtlayan doğrulanmış genişletilmiş bir Teknolojik Kabul modeli geliştirmektedir. Kullanıcının kişi izleme uygulamalarını kullanma niyeti ancak kullanıcının sağlığı ve güvenliği söz konusu olduğunda gerekli ödünler verilebilir.
Master of Technology in Information Technology. Institute of Graduate Studies and Research. Thesis (M.Tech.) - Eastern Mediterranean University, School of Computing and Technology, 2021. Supervisor: Asst. Prof. Dr. Mustafa Tanel Babagil.
Keywords: School of Computing and Technology; Contact tracing (Epidemiology)--Data processing; Computer Science--Cryptography; Data encryption (Computer science); Public Health--Health services administration; COVID-19; contact tracing; data privacy; digital contact tracing; mobile phone apps